2019
DOI: 10.1177/2471549219834192
|View full text |Cite
|
Sign up to set email alerts
|

Subscapularis in Reverse Total Shoulder Arthroplasty

Abstract: The use of reverse total shoulder arthroplasty (RSA) is becoming increasingly popular, but many biomechanical aspects are poorly understood. Particularly, the role and function of the subscapularis following RSA are unclear. Several clinical and biomechanical studies have analyzed its role in range of motion and stability. There is some evidence that the subscapularis is beneficial for stability but may reduce range of motion. This review provides an overview of the current literature, which suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For example, several studies have reported equivalent outcomes in IR with or without repair of the subscapularis. 3,6 In a subscapularissacrificing approach, one would suspect a difference in IR given that the primary tendon involved in IR is no longer functional. However, this study demonstrates that depending on the method of measuring outcome, such as PROMs as opposed to the ability to internal rotate with a smooth unassisted motion, there in fact may be a difference, which was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have reported equivalent outcomes in IR with or without repair of the subscapularis. 3,6 In a subscapularissacrificing approach, one would suspect a difference in IR given that the primary tendon involved in IR is no longer functional. However, this study demonstrates that depending on the method of measuring outcome, such as PROMs as opposed to the ability to internal rotate with a smooth unassisted motion, there in fact may be a difference, which was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies demonstrating a superior axial ROM for lateralized versus Grammont-style RSA are rare because they require surgeons to implant prostheses of varying designs. Furthermore, successful repair of the subscapularis is believed by many surgeons to influence postoperative ROM, although clinical evidence is variable [8][9][10].…”
Section: Introductionmentioning
confidence: 99%